Perencanaan Revitalisasi Zona Jogging Track dan Sport Area di Taman Cadika Medan - Sagala, Peranita; Wisdianti, Dara (PT. Arsil Reka Engineering, 2025)
Urban parks serve an important social dan ecological function as public spaces for active and passive recreation. Taman Cadika, located in Medan Johor Sub-district, Medan City, is one such urban park whose jogging track and sport area zone has degraded due to insufficient maintenance, resulting in damaged pavement, unmaintained vegetation, deteriorating furniture, and disorganized pedestrian-cyclist circulation. This study aims to formulate a revitalization plan for the jogging track and sport area zone of Taman Cadika through a forest-based design concept that restores the ecological, social, and aesthetic functions of the park. A descriptive qualitative case-study method was used, combining field observation, documentation, and comparative studies with Tebet Eco Park (Jakarta) and Taman Bunga Nusantara (West Java) as benchmark references. The results identify five critical sub-zones requiring intervention: the pedestrian zone, the central zone, the lakeside zone, the prayer room-toilet-parking zone, and the sports zone. The proposed design concept integrates a well-structured jogging track equipped with directional signage, thematic garden benches, an adventure track, and park lighting, supported by shade-tree planting following the urban forest approach. The findings are expected to serve as a reference for local government and park managers in improving the quality and sustainability of public green open space in Medan.